From natural river floodplains to sand pits – the role of primary and secondary habitats in the conservation of the rare tiger beetle Cylindera arenaria viennensis (Schrank, 1781) in Poland - Bobrek, Rafał (Ecological Questions, 2022)
Taxa naturally occupying ecosystems spatially restricted by anthropogenic land development sometimes find refuge in secondary habitats, taking advantage of conditions created by human management. One of them is Cylindera arenaria viennensis (Schrank, 1781), a rare tiger beetle originally inhabiting natural river valleys, especially open flat banks and dynamic alluvial zones. Today, these habitats across Europe have been heavily transformed, mostly losing their former natural character. Published data as well as those reported in this study indicate that all nine present-day (recorded no more than 30 years ago) localities of this beetle in Poland are found in secondary habitats. These comprise mainly functioning or abandoned opencast extraction sites of mineral deposits (like sand or gravel), which fits the pattern observed in other central European countries. Nevertheless, such sites, due to vegetation succession, drainage or inadequate management following cessation of extraction, are quickly losing their attractiveness for C. a. viennensis, ultimately driving local populations to disappear, which is likely to have occurred in one of the reported localities. Thereby, it is crucial to search for and then to protect any sites of this species found in primary habitats, as the long-term survival of populations of this beetle seems best ensured by the protection and restoration of original alluvial habitats found in natural river valleys.